THE MODEL DEVELOPMENT OF FINANCIAL POLICY FOR BASIC EDUCATION BASED ON THE PILLAR AE2 (Universitas Negeri Semarang, 2014)
There is a problem in policy implementation of budgeting for basic education in the study area, especially in providing budget which is less than normative standard so the disparity is not deniable. The objectives of the research are: (1) to analyze factual model of budgeting for basic education; and (2) to develop a modelofr financial policy for basic education. This study uses research and development approach. The data of the research consist of primary and secondary ones. Data collecting is conducted by using observation and interview. The analyses of data use descriptive-taxonomy. There are some main findings. Firstly, responding to the policy implementation, there is a significant disparity between factual budgeting and normative one in the basic education.Â Secondly, the model of financial policy for basic education which is developed, needs analysis based on AE2 (adequacy, equity and efficiency). The principle of adequecy is useful to eliminate the problem of financial disparity. The principle of Equity is useful to eliminate the gap among the schools with over standard of pupils and the schools with under standard of pupils. Then the prinsiple of efficiency is useful for supporting management in financial policy for basic education in the study area. Thirdly, based on the feasibility-test carried out by FGD and expert judgement, the model of financial policy for basic education based on AE2 in the area study, is in the category â€œhighly feasibleâ€. Based on the findings, it is better for stakeholder to develop and impmenent a financial policy for basic education, which is oriented to adequacy, equity and efficiency (AE2).